Postintubation Decline in Oxygen Saturation Index Predicts Mortality in COVID-19: A Retrospective Pilot Study. (26th May 2021) - Nozari, Ala; Mukerji, Shivali; Vora, Molly; Garcia, Alfonso; Park, Alyssa; Flores, Nicholas; Canelli, Robert; Rodriguez, Gerardo; Pinciroli, Riccardo; Nagrebetsky, Alexander; Ortega, Rafael; Quraishi, Sadeq A.
Abstract : Background . Acute respiratory failure from COVID-19 pneumonia is a major cause of death after SARS-CoV-2 infection. We investigated whether PaO2 /FiO2, oxygenation index (OI), SpO2 /FiO2, and oxygen saturation index (OSI), commonly used to assess the severity of acute respiratory distress syndrome (ARDS), can predict mortality in mechanically ventilated COVID-19 patients. Methods . In this single-centered retrospective pilot study, we enrolled 68 critically ill mechanically ventilated adult patients with confirmed COVID-19. Physiological variables were recorded on the day of intubation (day 0) and postintubation days 3 and 7. The association between physiological parameters, PaO2 /FiO2, OI, SpO2 /FiO2, and OSI with mortality was assessed using multiple variable logistic regression analysis. Receiver operating characteristic analysis was conducted to evaluate the performance of the predictive models. Results . The ARDS severity indices were not statistically different on the day of intubation, suggesting similar baseline conditions in nonsurviving and surviving patients. However, these indices were significantly worse in the nonsurviving as compared to surviving patients on postintubation days 3 and 7. On intubation day 3, PaO2 /FiO2 was 101.0 (61.4) in nonsurviving patients vs. 140.2 (109.6) in surviving patients, p = 0.004, and on day 7 106.3 (94.2) vs. 178.0 (69.3), p < 0.001 . OI was 135.0 (129.7) in nonsurviving vs. 84.8 (86.1) in surviving patients (p = 0.003 ) on day 3 and 150.0 (118.4) vs. 61.5 (46.7) (p < 0.001 ) on day 7. OSI was 12.0 (11.7) vs. 8.0 (10.0) (p = 0.006 ) on day 3 and 14.7 (13.2) vs. 6.5 (5.4) (p < 0.001 ) on day 7. Similarly, SpO2 /FiO2 was 130 (90) vs. 210 (90) (p = 0.003 ) on day 3 and 130 (90) vs. 230 (50) (p < 0.001 ) on day 7, while OSI was 12.0 (11.7) vs. 8.0 (10.0) (p = 0.006 ) on day 3 and 14.7 (13.2) vs. 6.5 (5.4) (p < 0.001 ) on day 7 in the nonsurviving and surviving patients, respectively. All measures were independently associated with hospital mortality, with significantly greater odds ratios observed on day 7. The area under the receiver operating characteristic curve (AUC) for mortality prediction was greatest on intubation day 7 (AUC = 0.775, 0.808, and 0.828 for PaO2 /FiO2, OI, SpO2 /FiO2, and OSI, respectively). Conclusions . Decline in oxygenation indices after intubation is predictive of mortality in COVID-19 patients. This time window is critical to the outcome of these patients and a possible target for future interventions. Future large-scale studies to confirm the prognostic value of the indices in COVID-19 patients are warranted.